Physical Activity and Quality of Life of Type 2 Diabetes Mellitus Patients: A Cross-sectional Study During the COVID-19 Pandemic: Aktivitas Fisik dan Kualitas Hidup Pasien Diabetes Melitus Tipe 2: Studi Cross-sectional Selama Masa Pandemi COVID-19 - Umardi , Adhelia Ananda; Widayati, Nur; Rondhianto (Jurnal Kesehatan Komunitas Indonesia, 2022)
The COVID-19 pandemic has impacted lifestyle changes, especially physical activity, which tends to decline. Lack of physical activity can worsen glycemic control in patients with type 2 diabetes mellitus, causing complications affecting their quality of life. This study aimed to analyze the correlation between physical activity and the quality of life of type 2 diabetes mellitus patients during the COVID-19 pandemic. This study used a descriptive correlational research design with a cross-sectional approach and 84 respondents obtained by a simple random sampling technique. Data were collected using a Physical Activity Questionnaire (GPAQ) and a Diabetes Quality of Life (DQOL) questionnaire and analyzed by the Kendall Tau correlation test with a significance level of 0.05. The results showed that 51.2% of respondents had moderate physical activity levels, and 57.1% had a high quality of life. Kendall's tau b test revealed a significant positive correlation between physical activity and the quality of life of type 2 diabetes mellitus patients during the COVID-19 pandemic (p-value = 0.015 and r = 0.251). Providing health education about the importance of physical activity is essential, especially during the COVID-19 pandemic, to enhance quality of life of type 2 diabetes mellitus patients.